The Principle of Force Majeure in Shariah: A Special Reference to Saudi Contract Law - Farhanin, Abdullah Asuhaimi; Zuhairah Ariff, Abd Ghadas (2018)
The principle of force majeure is mainly used in commercial and business contracts. According to Loweel (2008), the traditional rationale for force majeure clauses involved unanticipated events and impossibility of performance whilst the more recent practice has been to use force majeure provisions as a broader risk allocation tool. In Shari’ah, impossibility of performance due to changed circumstances is known as, Istihalah al-tanfidh. The principle of Quwa Qahira or Quwat al-Qanun is also observed to be broader than the English doctrine of frustration. It covers both supervening impossibility and circumstances where the performance has become substantially different to that initially agreed, resulting in the alteration of the rights and also the responsibilities under the contract. Special reference also be made to Saudi where in Saudi contract law, a force majeure event does not terminate the contract but merely suspends its applicability until performance becomes possible again. The authors in this paper applied doctrinal analysis as the research methodology of the topic.